(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Assess the level of anxiety and some factors related to anxiety of patients before planned surgery at the surgical departments of Vietnam-Sweden Hospital Uong Bi in 2024. Methods: Cross-sectional study on 197 patients undergoing surgery at 4 departments, Vietnam-Sweden Uong Bi Hospital from December 2023 to May 2024. The level of anxiety of patients before surgery was measured using the Zung (Self-Rating Anxiety Scale) self-assessment tool based on 4 groups of symptoms: cognitive, autonomic, motor and central nervous. Results: The anxiety rate of patients before surgery was 52.8%, with 30% of patients experiencing mild anxiety, 20.8% experiencing moderate anxiety, and no patients experiencing severe or very severe anxiety. Factors related to patient anxiety before surgery included gender,preoperative pain, receiving diagnostic information, and consultation about the surgical process. Conclusion: The anxiety rate of patients before surgery remains high. There is a need to improve health education and counseling for patients before surgery